Employability and mobility of Saudi literature and linguistics graduates in a transforming labor market - Alkahtani, Saeed Saleh; Ahmed, Syed Naeem; Alzahrani, Saeed Abdullah; Alghamdi, Kholoud Saeed; Alharbi, Eman Abdulrahman (Journal of International Students, 2026)
This empirical study integrates national labor market data with primary research to assess employability and mobility among Saudi Literature and Linguistics graduates under Vision 2030. Considering National Labor Observatory reports for benchmarks on employment rates, transition duration, and salary levels, the study combines these indicators with survey data from 200 graduates, employer evaluations from 50 employers, and qualitative focus groups. Descriptive statistics, logistic regression, t tests, and thematic analysis were conducted. In the sample, 37% of graduates were employed at the time of data collection, with a mean job search duration of 285 days and starting salaries below the national average. Internship participation and willingness to relocate were significant predictors of employment status. Employers rated graduate preparedness significantly lower than graduates’ self-assessments, particularly in digital literacy and applied bilingual proficiency.